Perancangan Sistem Informasi Persediaan Barang Berbasis Web Pada Toko Kuat - Irvan Triana; Agus Nugroho; Meisak, Despita (LPPM Universitas Dinamika Bangsa, 2024)
The Strong Shop is a shop that organizes business activities in the basic food, electronics and household furniture sectors. Currently, in inventory management at the Strong Store, they experience problems in the process of providing information on the inventory they have, where the process of counting goods is still carried out by means of physical counting. every time and takes a long time due to labor limitations, time constraints, and the many types of goods that exist. The purpose of this study is to analyze and study the problems that exist in the inventory system that runs on the Strong Store to help in designing the inventory system. To design the inventory system for the Strong Store using the PHP programming language and MySQL DBMS. The author develops the system using the waterfall method and uses the unified model language system model approach using use case diagrams, activity diagrams and class diagrams. This study resulted in an inventory system design to make it easier to search for certain information, for example information on goods data, supplier data, outgoing goods data, incoming goods data, supply reports, goods reports, incoming goods reports, outgoing goods reports related to inventory activities in Strong Shop.